Optimalisasi SIAKAD Berbasis Mobile melalui Redesign Antarmuka dan Pengalaman Pengguna dengan Pendekatan User-Centered Design - Hilmi Mubarok; Suryo Nugroho; Khalifah Brilianti Ramadhani; Nadjwa Naela Aziz; Fajar Mahardika (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2026)
The rapid development of mobile technology encourages educational institutions to provide academic systems that are easily accessible and efficient for users. However, many academic systems still have unintuitive interfaces and suboptimal user experiences, which hinder effective usage. This study aims to optimize the academic system on a mobile platform through a redesign of the User Interface (UI) and User Experience (UX) with a user-centered approach. The method used in this study is the User-Centered Design (UCD) approach, which involves users in every stage of the design process, including requirements analysis, wireframing, prototyping, and usability evaluation. Data were collected through observations, interviews, and questionnaires involving 50 respondents who are active users of the academic system. The results show a significant improvement after the redesign. The System Usability Scale (SUS) score increased from 62.5 (marginal category) to 85.2 (excellent category). The task success rate improved from 70% to 92%, while the average task completion time decreased by 35%. In addition, user satisfaction increased by 40% based on questionnaire results compared to the previous system. These findings indicate that implementing a user-centered UI/UX redesign significantly improves usability, efficiency, and user satisfaction in mobile-based academic systems